Rapid Regulation of an Anthranilate Synthase Aggregate by Hysteresis - Kane, J. F. (1973)
The anthranilate synthase aggregate from Bacillus subtilis is composed of two nonidentical subunits, denoted E and X, which are readily associated or dissociated. A complex of subunit E and X can utilize glutamine or ammonia as substrates in the formation of anthranilate. Partially purified subunit E is capable of using only ammonia as the amide donor in the anthranilate synthase reaction. The stability of the EX complex is strongly influenced by glutamine and by the concentrations of the subunits. Glutamine stabilizes the aggregate as a molecular species in which the velocity of the glutamine-reactive anthranilate synthase is a linear function of protein concentration. In the absence of glutamine the aggregate is readily dissociated following dilution of the extract; that is, velocity concaves upward as a function of increasing protein concentration. Reassociation of the EX complex is characterized by a velocity lag (or hysteretic response) before steady-state velocity for the glutamine-reactive anthranilate synthase is reached. We propose that association and dissociation of the anthranilate synthase aggregate may be physiologically significant and provide a control mechanism whereby repression or derepression causes disproportionate losses or gains in activity by virtue of protein-protein interactions between subunits E and X.